PERANCANGAN HUG MACHINE WRAP UNTUK ALAT TERAPI AUTISME - Suryo, Sumar Hadi; Raswan, Awan; Jamari, Jamari; Haryanto, Ismoyo (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
Today children born with the syndrome of autism is increasing. People with autism have a greater sensitivity to stimulation motor. This will cause them to feel discomfort when making physical contact with another person. Autism therapy can use the device as a media aide. Media autism therapies to be developed is the hug machine wrap. This media uses the principle of doing deep pressure therapy. At the hug machine made from fabric following the body shape of the user. The fabric binding of the user's body from shoulders to toes. Ballon added as a producer of pressure. Balloon filled with air pressure and the pressure can be regulated. Hug machine wrap designed to create deep pressure by inflating a balloon on inside, fabric pattern design that can cover the shoulder down to the legs will give equal emphasis. Therapeutic application of deep pressure on children with autism are expected to assist in receiving physical contact to the social environment and increase peace of children with autism